Dispelling the Malaria-Typhoid Co-infection Myth in Nigeria: A Literature Review - Olawale Akinola (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2024)
Malaria and typhoid fever are public health concerns in Nigeria, with high prevalence rates. The perception of a widespread co-infection between these diseases may be misleading, due to limitations in diagnostic methods, particularly the Widal test for typhoid fever. This literature review examines the prevalence of malaria-typhoid co-infection in Nigeria and identifies factors contributing to misdiagnosis, including non-specific symptoms, limited diagnostic resources, and the diagnostic accuracy of tests employed. Additionally, the review discusses the implications of misdiagnosis, such as the overuse of broad-spectrum antibiotics leading to a rising incidence of antimicrobial resistance. Strategies to address this issue are explored, emphasizing the need for improved diagnostic methods, enhanced healthcare provider education, and comprehensive health education campaigns to empower patients and curb antibiotic misuse. While acknowledging limitations in available research done in Nigeria, this review underscores the urgency of addressing the malaria-typhoid co-infection myth to improve healthcare outcomes and combat antimicrobial resistance in Nigeria.